Clinical and genetic investigations of five Chinese families with Birt–Hogg–Dubé syndrome: a long-term follow-up study - Kang, Xi; Guo, Ting; Basit, Ali; Liu, Lv; Luo, Hong (Frontiers in Medicine, 2025)
Birt–Hogg–Dubé syndrome (BHDS), an autosomal dominant disease, is caused by germline mutations in the folliculin (FLCN, NM_144997) gene. This rare disorder is characterized by a clinical triad, which includes fibrofolliculomas (FFs), renal cell carcinoma (RCC), and pulmonary manifestations such as multiple pulmonary cysts (PCs) and pneumothorax. To investigate the clinical features and genetic mutations of five unrelated BHDS families in a long-term follow-up study at the Second Xiangya Hospital of Central South University, five families and their affected patients, who met the clinical and histological criteria for BHDS and were confirmed to have FLCN germline mutations, were evaluated. All participants underwent a comprehensive physical examination along with other relevant tests. Three novel mutations (c.246C > A, c.625_626insAGGCAGAGCAGTTTGGAT, and c.1542_1542delA) and one previously reported mutation (c.1429C > T) in the FLCN gene were identified. These mutations are predicted to cause truncation of the folliculin protein, likely resulting in decreased folliculin expression. Our study expands the genetic landscape associated with BHDS and provides valuable insights for future genetic counseling and the clinical management of individuals with BHDS.